RELIGIOUS MODERATION BASED ON SOCIO-HISTORICAL INTERPRETATION OF TOLERANT VERSES - Latifah, Ipah (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
This study addresses the urgency of Religious Moderation in multicultural Indonesia amidst rising cases of intolerance. The core problem lies in how to apply Socio-Historical Exegesis to re-contextualize the Quranic verses on tolerance, thereby establishing a solid theological foundation for the Religious Moderation program. The study aims to formulate an accountable and Qur'an-based theological concept of Religious Moderation. The method employs qualitative research using the Tafsir Maudhu’i (Thematic Exegesis) approach combined with Socio-Historical analysis, specifically utilizing Fazlur Rahman’s Double Movement framework on key verses (e.g., Q.S. Al-Kafirun: 6, Al-Baqarah: 256, and Mumtahanah: 8-9. The findings indicate that contextual interpretation successfully distinguishes the universal ethical message (social tolerance) from the specific historical context (theological boundary). Conclusion: Religious Moderation is not merely a political policy but an embodiment of the Quran’s essential teachings that uphold the freedom of belief and universal justice. Socio-Historical Exegesis proves capable of providing a comprehensive theological argument to counter extremist narratives.